Mathematical critical thinking in ethno-controversial problems: A logical-mathematical intelligence perspective - I Gusti Ngurah Pujawan; I Putu Pasek Suryawan; I Gusti Nyoman Yudi Hartawan; I Made Suarsana (Indonesian Journal of Educational Development (IJED), 2026)
Mathematical critical thinking ability is a crucial skill that should be developed in mathematics education, particularly in addressing complex and contextual problems. This study aims to describe the mathematical critical thinking skills of Grade 10 senior high school students in solving ethno-controversial mathematical problems viewed from the level of logical–mathematical intelligence. This study employed a descriptive qualitative approach, with 6 grade 10 students from SMA Negeri 2 Singaraja as subjects, selected based on high, medium, and low levels of logical–mathematical intelligence. Data were collected through a written test based on ethno-controversial problems, a logical–mathematical intelligence questionnaire, semi-structured interviews, and documentation of students' work. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, referring to the indicators of mathematical critical thinking, namely interpretation, analysis, evaluation, and inference. The results of the study indicate that students with high logical–mathematical intelligence consistently meet most indicators of mathematical critical thinking, although they still show shortcomings in systematically presenting conclusions. Students with moderate logical–mathematical intelligence demonstrate fairly good mathematical critical thinking abilities in the indicators of interpretation and analysis; however, they still experience difficulties in the indicators of evaluation and inference. Meanwhile, students with low logical–mathematical intelligence show limitations in almost all indicators of mathematical critical thinking. These findings suggest the need for differentiated instructional strategies tailored to students' levels of logical–mathematical intelligence.